The Implementation of School Literacy Movement in the Perspective of Mortimer Adler and Charles Van Doren - Septiana Purwaningrum; Syamsul Arifin; Akhsanul In'am; Khozin (State Islamic Institute of Madura, 2021)
This study aims to describe the implementation of the SLM in MTsN 2 Kediri City , the benefits of applying SLM, the constraints faced , and to analyze the implementation of the SLM with reading theory from Mortimer Adler and Charles Van Doren. The research method used was qualitative with the type of case study research. The subjects of this study were the school principal, deputy school principal in the curriculum, Indonesian Language teachers, and students. Data obtained through in- depth interviews, observation, and documentation. Next data were analyzed using the Miles and Huberman model which included the stages of selecting data, presenting data, and drawing conclusions. To check the validity of the data, researchers extended the observation and triangulation of sources and data collection techniques. The results of this study are: 1) The SLM in MtsN 2 Kediri City is implemented through reading corner activities; Wall magazine; environmental conditioning that is full of motivational sentences; habit of reading the Qur'an; as well as assignments on Indonesian Language subjects, the form of assignments such as: summarizing some types of books such as old novels, biographies, fantasy stories and popular knowledge; 2) The benefits of implementing this program are students being diligent in reading, trained in composing sentences, getting to know the types of books, and increasing their knowledge; 3) The constraints faced this program are the lack of available reading material in the library; students have difficulty in getting the type of books required; and difficulties in summarizing thick books; and 4) The implementation of SLM in MTsN 2 Kediri City is categorized in the third level of reading theory of Mortimer Adler and Charles Van Doren. It can be seen from the type of task assigned for participants learners to review book until the analysis, it is to display the advantages as well as the shortage of books read.